Acquired antiprothrombin antibodies: an unusual cause of bleeding. (7th January 2013) - Carvalho, Cristiana; Viveiro, Carolina; Maia, Paulo; Rezende, Teresa
Abstract : Acquired inhibitors of coagulation causing bleeding manifestations are rare in children. They emerge, normally in the context of autoimmune diseases or drug ingestion, but transient and self-limiting cases can occur after viral infection. We describe, an otherwise healthy, 7-year-old girl who had gingival bleeding after a tooth extraction. The prothrombin time (PT) and the activated partial thromboplastin time (APTT) were both prolonged with evidence of an immediate acting inhibitor (lupic anticoagulant). Further coagulation studies demonstrated prothrombin (FII) deficiency and prothrombin directed (FII) antibodies. The serological tests to detect an underlying autoimmune disease were all negative. The coagulation studies normalised alongside the disappearance of the antibody. This article presents lupus anticoagulant hypoprothrombinaemia syndrome (LAHS) as a rare case of acquired bleeding diathesis in childhood.